Política pública como componente dos ecossistemas de empreendedorismo: desafios da elaboração e implementação - Souza Neto, José Batista de (2023)
This research defined as a research problem to understand how public policies for access to markets that boost the entrepreneurial ecosystem of MSEs are designed and implemented. The general objective of this research was to understand the process of elaboration and implementation of a public policy to support the entrepreneurial ecosystem of micro and small companies through the SEBRAE system, considering the national context and the context in the State of São Paulo. Considering that public policies are constituent elements of entrepreneurship ecosystems that influence the creation and development of enterprises from the action of the entrepreneur, at the end of the research, it is expected to achieve the results for the following specific objectives: (a) understand how public market access policies for MSEs are designed and implemented; and (b) offer instruments for implementing public market access policies. Field research was conducted based on action research, with a qualitative and longitudinal approach to the data. Data collection was based on narratives produced since 2019 when the decision to implement the Comércio Brasil program was made, a public policy focused on generating access to markets for MSEs. The narratives were analyzed using the document analysis and narrative analysis method. The research contributed to emphasize the relevance of public policies on market access for MSEs and reinforced the legitimacy to SEBRAE as a protagonist in the implementation of these public policies in the entrepreneurship ecosystem. Action Research was recognized as a method of scientific and practical intervention, just as Design Thinking emerged as a relevant method for the elaboration of public policies, complementing the Public Policy Cycle. The research reveals that the elaboration and implementation of public market access policies are complex, dynamic, anthropological, changeable and participatory processes. The research recognizes the dual roles of the researcher-manager and the relevance of their participation.